Work Environment, Employee Motivation, and Discipline as Drivers of Employee Performance in Local Government-Owned Bank - Fathur Rozi, Ahmad; Sundari, Ariefah; Syaikuddin, Ahmad Yani (Faculty of Economics and Business, Universitas Klabat, 2024)
The objective of this research is to investigate the impact of the work environment, motivation, and discipline on employee performance in Local Government-owned bank. The study was conducted at Bank Daerah Lamongan, using a sample of 69 employees out of a total of 218. The sample size was determined using the Slovin formula, and data collection was carried out through random sampling. A quantitative method was applied, with data processed using SPSS to conduct data quality tests, classical assumption tests, and to assess the partial and simultaneous effects of these work factors on employee performance. Several hypotheses were tested regarding the relationships between the work environment, employee motivation, and work discipline. It was anticipated that the work environment would significantly influence employee performance. The analysis yielded the following results: Based on the t-test, the work environment showed a significant impact on employee performance. Similarly, the results indicated that both motivation and discipline also had significant effects on performance. The f-test results further confirmed that the work environment, motivation, and discipline had a combined and individual influence on employee performance at Bank Daerah Lamongan. Among these factors, the work environment was found to have the most dominant impact on performance.